Determination of septicaemia causative agents in ruminants - Faridon, Batrisyia Syazana (2021)
Domestic ruminant of economic importance includes buffalo, cattle, goats, sheep, and deer. These animals are known for their roles in conversion of fibrous feed into animal protein for human consumption. Over the years, despite remarkable enhancement has been made in regards to ruminant production, the diseases incidence also goes along in increasing manner. Recent studies of common health problems in ruminants in Malaysia showed that septicaemia as the leading threat to ruminant’s sustainability as septicaemia covered 63.3% health problems involving circulatory system. The study also depicted Escherichia coli, Pasteurella sp., and Klebsiella pneumoniae as the most important bacteria that contributes to septicaemia or bacterial pneumonia in ruminants. Despite this, no study was conducted to understand common pathogens and risk factors of septicaemia in veterinary medicine. Septicaemia is the presence of pathogen and its toxin in the bloodstream of a host, potentially leading to acute death of the host. It could be caused by wide range of pathogens, particularly bacteria with numerous potential points of entry and risk factors. The objectives of this study were to (1) identify and analyze the common microorganisms, points of entry, and risk factors associated with septicaemia in ruminants, (2) isolate, identify, and perform phylogenetic analysis of common bacteria causing septicaemia in ruminants, and (3) analyze the antibiotic susceptibility profiles of these bacteria. This study involved two parts; a retrospective study and a prospective study. In the retrospective study, data of post-mortem cases of small ruminants (sheep, goat, and deer) and large ruminants (cattle, buffalo, and gaur) diagnosed with septicaemia at the Post- mortem Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia (UPM) between the years of 2007 and 2017 were used for analysis. It was later observed that septicaemia was more important in the small ruminants therefore the prospective study was conducted only in the small ruminants. A total of 20 carcasses of small ruminants with septicaemia submitted to the Post-mortem Laboratory, UPM between the year 2018 and 2019 were diagnosed with septicaemia based on isolation of similar microorganism in more than three internal organs (lung, liver, heart, or kidney). For the retrospective study, it was observed that the three most commonly isolated microorganisms in cases of septicaemia in small ruminants are E. coli (66.2%), K. pneumoniae (23.2%) and Pasteurella sp. (10.6%). On the other hand, E. coli (50.9%), K. pneumoniae (40%), Staphylococcus aureus (9.1%) are the most commonly isolated septicaemia-causing bacteria in large ruminants. For both small and large ruminants, gastrointestinal tract has been found to be the most common point of entry for septicaemia, which was statistically significant (p<0.05) compared to respiratory tract, reproductive tract, integumentary, and other body systems. Underlying infection in small and large ruminant is the significant (p<0.05) risk factor for septicaemia. In the prospective study, E. coli was found to be the most common microorganism associated with septicaemia with a total of 24 isolates (29.6 %), seven isolates of S. aureus (8.6 %), and six isolates of K. pneumoniae (7.4 %) compared to all other 26 different microorganisms with a total of 81 isolates. Escherichia coli was confirmed as the most important bacteria species in causing septicaemia in ruminants. Antibiotic susceptibility tests showed that most isolates of E. coli were resistant towards Tetracycline (30 μg) involving 17 isolates. This is followed by resistance towards Ampicillin (10 μg) and Amoxycillin (10 μg) involving 16 E. coli isolates, and Streptomycin (10 μg) with nine isolates. Escherichia coli is the most common bacterial isolated from cases of septicaemia especially those originated from the gastrointestinal tract and the respiratory tract. The antibiotic sensitivity test showed high percentage of resistance that requires strategies to prevent emerging of multiple-drug resistance microorganism in the near future.